Investigation on changing pattern of health status of juvenile Hypophthalmichthys molitrix from farming systems in Bangladesh - Kamal Gosh; Gias Uddin Ahmed; Mst Nahid Akter (Journal of Fisheries, 2016)
An experiment was carried out to investigate the health status of Hypophthalmichthys molitrix among three different fish farms at Mymensingh district of Bangladesh. Fish sampling and water quality parameters were collected on a monthly basis. Samples of skin, muscle, gills, liver and kidney were examined through histological technique. Results from water quality parameters suggested that water temperature had a distinct effect on fish health of H. molitrix, which was mostly evident during the colder months. Infectious symptoms were usually evident in July to October and the severity of pathology was increased in November and December. These were evident from their clinical signs that include scale loss, haemorrhagic lesion, and reddish spots or from their histopathological symptoms such as necrosis, pyknosis, inflammation, haemorrhage, hypertrophy, missing of gill lamellae, vacuums, tubular and pillar cells degeneration, inflammation, clubbing, and suspected bacterial colonies. Results suggest that the health condition of the fishes from BAU fish farm was the best over the other two farms, whereas Government fish farm followed by NGO fish farm were severely affected with EUS, protozoan and bacterial infection. Moreover, internal organs like liver and kidney were more affected than skin, muscle and gills.